Mobile app for virtual study room - Ng, Yu Zhe (Nanyang Technological University, 2023)
This project aims to create a mobile application for students to learn and receive information if there was a case whereby online-schooling is required. The goal of the project is to have the application streamline the process of learning and receiving information from their teachers and professors if there was a case of mass isolation needed, such as the COVID-19 pandemic that affected schooling from 2020 to 2022 and beyond.